2022
DOI: 10.3390/biomedicines10112809
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint Molecules and Glucose Metabolism in HIV-Induced T Cell Exhaustion

Abstract: The progressive decline of CD8+ cytotoxic T cells in human immunodeficiency virus (HIV)-infected patients due to infection-triggered cell exhaustion and cell death is significantly correlated with disease severity and progression into the life-threatening acquired immunodeficiency syndrome (AIDS) stage. T cell exhaustion is a condition of cell dysfunction despite antigen engagement, characterized by augmented surface expression of immune checkpoint molecules such as programmed cell death protein 1 (PD-1), whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 138 publications
0
5
0
Order By: Relevance
“…Blocking inhibitory receptors such as PD-1, CTLA-4 or Lag-3 have reversed this exhausted state in clinical trials of T cells in cancer [88]. Additionally, metformin has been utilized in HIV-induced T cell exhaustion treatment to increase glucose import and subsequent cellular energy production [89]. Meanwhile, knocking out CD36 in Tregs of a hypoxic tumor microenvironment allowed lymphocytes to kill target cells while sustaining homeostasis, pointing to the importance of considering metabolic components like these in therapeutic treatments [90].…”
Section: Implications Of Altered Lipid Metabolism In Me/cfs T Cellsmentioning
confidence: 99%
“…Blocking inhibitory receptors such as PD-1, CTLA-4 or Lag-3 have reversed this exhausted state in clinical trials of T cells in cancer [88]. Additionally, metformin has been utilized in HIV-induced T cell exhaustion treatment to increase glucose import and subsequent cellular energy production [89]. Meanwhile, knocking out CD36 in Tregs of a hypoxic tumor microenvironment allowed lymphocytes to kill target cells while sustaining homeostasis, pointing to the importance of considering metabolic components like these in therapeutic treatments [90].…”
Section: Implications Of Altered Lipid Metabolism In Me/cfs T Cellsmentioning
confidence: 99%
“…With regard to the use of anti-PD-1/PD-L1 as adjuvants, a difference in efficacy may be influenced by various factors, such as the type of antigen and underlying mechanisms of protective responses. Moreover, several pathways aside from the PD-1/PD-L1 axis are involved in the establishment of T cell exhaustion and include the expression of other molecules, such as cytotoxic T-lymphocyte antigen-4 (CTLA-4), TIM-3, LAG-3 and T cell immunoreceptor with immunoglobulin and ITIM domains (TIGIT) that all regulate T cell function through independent mechanisms [ 30 ]. Thus, the combination of antibodies to target different T cell exhaustion pathways may be more effective than the use of individual antibody treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that T-cell dysfunction is associated with glucose metabolism disorders [44], and the competition between tumor cells and CD8 + T cells for limited glucose leads to reduced CD8 + Tcell effector function [45]. However, Chang et al found that in exhausted CD8 + T cells in vitro, it was di cult to increase their effector capacity even if superphysiological levels of glucose were given [46].…”
Section: Discussionmentioning
confidence: 99%